Taking crime guns seriously: A socio-material perspective - Goldsmith, Andrew (Criminology & criminal justice, 2022)
This article argues that guns, as objects used in and for crime, have received insufficient criminological attention. It proposes a socio-material perspective for taking crime guns seriously as material agents in the ways many serious crimes are planned and executed. Drawing in part upon affordance theory, the perspective links the ‘objective’ physical properties of guns to their allure and take up for the purposes of carrying out crime. Guns are powerful organising objects in the commission of crime, it is argued, capable of provoking as well as enabling a range of threatening and harmful activities. The perspective is developed drawing upon interview data from a large qualitative study of convicted gun criminals. These data enable the notion of materiality to be considered at different stages of criminal career, particularly prior to first criminal gun use through to enforced or voluntary desistance. The article concludes with a consideration of policy options suggested by the socio-material perspective. In a post-Covid 19 world in which guns have gained greater salience in many countries, it is argued that the need to ‘dematerialise’ gun attraction and use has never been greater.